2011
DOI: 10.2337/db11-0455
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic Glucagon Action Is Essential for Exercise-Induced Reversal of Mouse Fatty Liver

Abstract: OBJECTIVEExercise is an effective intervention to treat fatty liver. However, the mechanism(s) that underlie exercise-induced reductions in fatty liver are unclear. Here we tested the hypothesis that exercise requires hepatic glucagon action to reduce fatty liver.RESEARCH DESIGN AND METHODSC57BL/6 mice were fed high-fat diet (HFD) and assessed using magnetic resonance, biochemical, and histological techniques to establish a timeline for fatty liver development over 20 weeks. Glucagon receptor null (gcgr−/−) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…Studies in patient cohorts have demonstrated an inverse association between physical activity and fitness and NAFLD (8,31), whereas training interventions (17,23,40) can impact on NAFLD in a positive manner. Similar findings have been made using various rodent models (3,35).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Studies in patient cohorts have demonstrated an inverse association between physical activity and fitness and NAFLD (8,31), whereas training interventions (17,23,40) can impact on NAFLD in a positive manner. Similar findings have been made using various rodent models (3,35).…”
supporting
confidence: 74%
“…Therefore, the improvements observed with exercise training may have a significant relation to the human condition. Interestingly, exercise training may also impact upon cholesterol homeostasis in the liver, as there was a decrease in accumulated cholesterol esters, which have previously been shown to be increased with high-fat feeding (3). Together, these changes in hepatic lipid levels correlated with the overall health of the liver given the marked improvement in liver function as measured by AST and ALT levels (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…These effects seem to counteract any hepatic anabolism. Indeed, exercise-stimulated glucagon receptor activation was found to be essential for treating high-fat dietinduced NAFLD in non-diabetic mice [121]. This further complicates the understanding of liver steatosis and glycogen accumulation in type 1 diabetes.…”
Section: Glucagonmentioning
confidence: 99%
“…16 Similarly, significant reductions in hepatic lipid contents and metabolic complications after exercise training were observed in Otsuka Long-Evans Tokushima Fatty (OLETF) rats 17 and obese Zucker rats 18 and mice. 19 Thus, it has been reported that compared with EX or CR alone, the combination of EX and CR is more effective at improving NAFLD and its metabolic complications, 20 although the mechanisms underlying the additive benefits are unclear. However, recent studies have suggested that the adiponectin receptor-mediated signaling pathway may play an important role in mediating the additive benefits of the combination of EX and CR in the treatment of NAFLD.…”
Section: Introductionmentioning
confidence: 99%